If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x-7(-7-4x)=2(3x-4)
We move all terms to the left:
-5x-7(-7-4x)-(2(3x-4))=0
We add all the numbers together, and all the variables
-5x-7(-4x-7)-(2(3x-4))=0
We multiply parentheses
-5x+28x-(2(3x-4))+49=0
We calculate terms in parentheses: -(2(3x-4)), so:We add all the numbers together, and all the variables
2(3x-4)
We multiply parentheses
6x-8
Back to the equation:
-(6x-8)
23x-(6x-8)+49=0
We get rid of parentheses
23x-6x+8+49=0
We add all the numbers together, and all the variables
17x+57=0
We move all terms containing x to the left, all other terms to the right
17x=-57
x=-57/17
x=-3+6/17
| 4(2x-6)=27 | | 4.6-4x=-22 | | g=4+0.93/3 | | 4(w+8)=7+4w | | -4(u-8)=-6u+22 | | 16.57=3g+3.64 | | 31-2(6x-50)=47 | | 6(x-7=10(x+4) | | 3(x-16)=56 | | b(b-3)=10 | | 2(4x)+2(3x+2)=116 | | 8x-(2x+8)=8x-20 | | 8x+11+14x-1=0 | | -2(8v-9)+2v=4(v+4) | | 18-4k=-10=4k | | 1/2(2x-20)=2(3x-5) | | 4(3x+7)−6(4x−7)=11x+3(4x−6) | | 12(x-2)+3x=1.2(x+6)+2 | | 11x-1=x+9 | | 55=55-11u | | 28a=-84 | | 3d-5=-2+3d | | -8y-13=14y+11 | | 7(v-1)-5=-6(-5v+4)-5v | | x+9=11x-1 | | 2x+3=3x−1 | | a/5-4=16 | | 12.12=2g+3.74 | | 9(11)+25+17y+15=180 | | -20=3/2w | | 4/3x-4/3=-1/3x-1/2 | | 7v-36=5(v-8) |